The Role of JAK2 in Myeloproliferative Diseases Diagnosis - Yudith Annisa Ayu Rezkitha; S. Ugroseno Yudho Bintoro; Ami Ashariati (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Janus Kinase 2 (JAK2) plays an important role in mediating transduction signal of hematopoiesis, including in the pathogenesis of Myeloproliferative diseases (MPD). Various studies have been carried out to identify the position of aleles in tyrosine encoding mutations. Although the effect of JAK2 mutations is still not fully understood, the discovery of these mutations might be able to differentiate the types of polycythaemia vera, essential thrombocytemia, and primary myelofibrosis with malignant abnormalities. WHO has revised the MPD diagnosis criteria following this finding. This review will discuss the role of JAK2.